Inhibition of the miR‐193b‐3p protects against oxidized low‐density lipoprotein‐induced HUVECs injury by upregulating ALDH2. (15th November 2021) - Bai, Yunpeng; Wang, Mei; Yang, Yin; Liu, Xiankun; Chen, Qingliang; Guo, Zhigang
Abstract: Atherosclerosis (AS) is the most dangerous factor for human death, which is a lipid‐driven chronic inflammatory disorder of the arteries. Growing evidence has showed that microRNAs play an important role in AS. However, the role of mir‐193b‐3p in atherosclerosis has been poorly studied to date. Therefore, we focused on the potential role of miR‐193b‐3p in atherosclerosis. The expressions of miR‐193b‐3p in the serum of AS patients were detected. We also established an oxidized low density lipoprotein (ox‐LDL)‐induced human umbilical vein endothelial cells (HUVECs) apoptosis model in vitro. The mRNA and protein levels of target molecules were detected by RT‐qPCR and Western blotting. Apoptosis of HUVECs was determined by Annexin V/PI staining on a flow cytometry. The potential molecular targets of miR‐193b‐3p were investigated by applying such technologies as dual‐luciferase reporter and RIP assay. Our study showed that miR‐193b‐3p expression level was significantly lower in AS patients than controls. ROC curve analysis showed that the areas under the curve (AUC) of plasma miR‐193b‐3p was 0.859. We also found that miR‐193b‐3p was decreased in ox‐LDL‐induced HUVECs and knockdown of miR‐193b‐3p suppressed ox‐LDL‐induced HUVECs injury. By using bioinformatics analysis, aldehyde dehydrogenase (ALDH2) was predicted as a downstream target of miR‐193b‐3p. The ALDH2 gene is also involved in the development of atherosclerosis. Meanwhile, inhibition of miR‐193b‐3p and ALDH2 protects ox‐LDL‐induced HUVECs against endoplasmic‐reticulum (ER) stress. In conclusion, inhibition of miR‐193b‐3p was able to suppress ox‐LDL‐induced injury in AS through targeting ALDH2 and reducing ER stress.